Antibacterial self-cleaning wall cloth and preparation method thereof
By reacting the polyacrylate fabric with aniline and surface treatment liquid, and introducing modified zinc oxide titanium dioxide composite material and POSS material, an antibacterial self-cleaning wall cloth is produced, which solves the problem of microbial reproduction caused by the wall cloth being easily absorbed by oil and sweat, and achieves multiple effects of antibacterial, self-cleaning, flame retardant, antistatic and corrosion resistance.
Patent Information
- Application Number
- CN202411942898.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-22
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Wall cloth is easy to absorb oil and sweat metabolically secreted by the human body, leading to the reproduction of microorganisms and the spread of bacteria, affecting the comfort and lifespan of use.
The antibacterial self-cleaning wall cloth is prepared by reacting polyacrylate fabric with aniline and surface treatment liquid. The antibacterial and self-cleaning effect is achieved through the use of modified zinc oxide titanium dioxide composite materials and POSS materials.
It realizes the antibacterial and self-cleaning functions of wall cloth, improves the flame retardant, antistatic and corrosion resistance of the material, extends the service life and improves the comfort of use.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabrics, in particular to an antibacterial self-cleaning wall cloth and a preparation method thereof. Background Art
[0002] Wall covering is also known as "wall cloth". As the name suggests, it is a special "paper" and "cloth" that is pasted on the wall for decoration. It is a commonly used decorative material for interior walls of buildings. Printing or embossing is applied to the base cloth. The patterns used are mostly geometric shapes and floral patterns. Embroidery technology is also used to make wall coverings, which can beautify the environment, improve visual effects and enhance the overall sense of the room.
[0003] In recent years, the application of wall cloth has become more and more extensive, but wall cloth can easily absorb metabolites such as oil and sweat secreted by human metabolism, thus providing excellent conditions for the attachment, breeding and reproduction of microorganisms and pathogens. Under suitable temperature, moisture or humidity conditions, a large number of microorganisms will multiply, accompanied by irritating odors, which will aggravate the spread of pathogens and affect the comfort and service life of the wall cloth. Therefore, this article introduces an antibacterial self-cleaning wall cloth and its preparation method. Summary of the invention
[0004] The purpose of the present invention is to provide an antibacterial self-cleaning wall cloth and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] An antibacterial self-cleaning wall cloth, which is prepared by reacting polyacrylate fabric with aniline and surface treatment liquid in sequence;
[0006] The polyacrylate fabric is prepared by mixing polyacrylate emulsion and modified zinc oxide titanium dioxide composite material, spinning and weaving;
[0007] The polyacrylate emulsion is prepared by polymerizing an olefin mixed liquid;
[0008] The modified zinc oxide titanium dioxide composite material is prepared by mixing zinc oxide and titanium dioxide sol, drying, and then reacting with trimethoxysilane and modified POSS in sequence;
[0009] The modified POSS is prepared by reacting methyltrimethoxysilane and allyltrimethoxysilane.
[0010] A method for preparing an antibacterial self-cleaning wall cloth, the method for preparing the antibacterial self-cleaning wall cloth mainly comprises the following preparation steps:
[0011] (1) Lithium hydroxide monohydrate, deionized water, acetone and methanol are mixed in a mass ratio of 4-6:3-5:170-176:23-25, stirred at 75-85°C and 200-300 r / min for 3-5 minutes, methyltrimethoxysilane with a mass of 11-13 times the mass of deionized water is added at a uniform rate within 5-7 minutes, sodium hydroxide solution with a mass of 62-65 times the mass of deionized water is added, stirring is continued for 100-140 minutes, filtered, washed with acetonitrile for 4-6 times, and heated at 70-80°C. Drying for 10 to 14 hours to obtain modified polysiloxane; mixing the modified polysiloxane with ethanol in a mass ratio of 1:4.5 to 5.5, stirring at 18 to 22°C and 200 to 300 r / min for 3 to 5 minutes, uniformly adding allyl trimethoxy silane in an amount of 0.04 to 0.05 times the mass of ethanol and tetraethyl ammonium hydroxide solution in an amount of 0.035 to 0.045 times the mass of ethanol within 50 to 70 minutes, continuing stirring for 35 to 37 hours, filtering, and washing with acetonitrile for 4 to 6 times to obtain modified POSS;
[0012] (2) mixing butyl titanate, diethanolamine and ethanol in a mass ratio of 1:1 to 1.2:17 to 18, stirring at 200 to 300 r / min for 8 to 12 minutes, adding an ethanol aqueous solution 13 to 14 times the mass of butyl titanate at a uniform rate within 8 to 10 minutes, and continuing to stir for 30 to 40 minutes to obtain a titanium dioxide sol; immersing zinc oxide in the titanium dioxide sol for 2 to 3 minutes, filtering, drying at 90 to 110° C. for 8 to 12 minutes, and then keeping warm at 490 to 510° C. for 50 to 70 minutes to obtain a zinc oxide titanium dioxide composite material; mixing the zinc oxide titanium dioxide composite material and trimethoxysilane Alkane and isopropanol are mixed in a mass ratio of 8-12:1:30-50, stirred at 85-95°C and 200-300r / min for 5-7h, centrifuged to obtain a solid, washed with deionized water for 3-5 times, and dried at 90-100°C for 2-4h to obtain a pre-modified zinc oxide titanium dioxide composite material; the pre-modified zinc oxide titanium dioxide composite material, modified POSS, chloroplatinic acid and isopropanol are mixed in a mass ratio of 1:0.3-0.5:0.03-0.05:3-3.4, stirred at 60-70°C and 200-300r / min for 4-6h to obtain a modified zinc oxide titanium dioxide composite material;
[0013] (3) heating 4-methylcyclohexanone to 140-144° C., adding 3-5 times the mass of 4-methylcyclohexanone olefin mixture and 0.03-0.05 times the mass of olefin mixture at a uniform rate over 4-6 hours, heating to 145-155° C., continuing the reaction for 100-140 minutes, then cooling to room temperature, and adjusting the pH to 6.5-7.5 with dimethylethanolamine to obtain a polyacrylate emulsion;
[0014] (4) electrospinning the spinning solution at a spinning flow rate of 0.18 to 0.22 ml / h, a spinning voltage of 16 to 18 kV, and a receiving distance of 14 to 16 cm, standing for 6 to 8 hours, and naturally cooling to room temperature to obtain modified polyacrylate fiber, which is woven into a fabric to obtain a polyacrylate fabric;
[0015] (5) The polyacrylate fabric is immersed in an aniline aqueous solution and ultrasonically treated for 50 to 70 minutes. An ammonium persulfate aqueous solution of equal mass to the aniline aqueous solution is added at a uniform rate within 160 to 200 minutes. The polyacrylate fabric is taken out and allowed to stand for 18 to 22 hours. The polyacrylate fabric is washed with ethanol for 3 to 5 times and dried at -10 to 0°C for 22 to 24 hours to obtain a modified polyacrylate fabric. 1 to 2 mL of the surface treatment liquid is evenly coated on each square centimeter of the surface of the modified polyacrylate fabric. The surface is allowed to stand for 4 to 5 hours at 120 to 140°C under nitrogen protection. The coating and drying are repeated for 3 to 5 times. The fabric is washed with acetone for 3 to 5 times and vacuum dried at -10 to -1°C for 22 to 24 hours to obtain a wall covering.
[0016] As an optimization, the ethanol aqueous solution in step (2) is prepared by uniformly mixing ethanol and deionized water in a mass ratio of 8-9:4-6.
[0017] As an optimization, the zinc oxide in step (2) is nano zinc oxide with a particle size of 50 nm.
[0018] As an optimization, the olefin mixture in step (3) is prepared by uniformly mixing methyl methacrylate, isooctyl acrylate, glycidyl methacrylate and butyl acrylate in a mass ratio of 8-10:4-6:2-3:12-16.
[0019] As an optimization, the spinning solution in step (4) is prepared by uniformly mixing a polyacrylate emulsion and a modified zinc oxide-titanium dioxide composite material in a mass ratio of 1:0.1-0.2.
[0020] As an optimization, the aniline aqueous solution in step (5) is prepared by uniformly mixing aniline and water in a mass ratio of 1:9 to 11.
[0021] As an optimization, the ammonium persulfate aqueous solution in step (5) is prepared by uniformly mixing ammonium persulfate and deionized water in a mass ratio of 1:18 to 22.
[0022] As an optimization, the surface treatment liquid in step (5) is prepared by uniformly mixing trifluoropropylene, xylene and diisopropylbenzene peroxide in a mass ratio of 1:18-22:0.6-0.8.
[0023] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0024] When preparing the antibacterial self-cleaning wall cloth, the present invention comprises the following steps: reacting methyltrimethoxysilane and allyltrimethoxysilane to obtain modified POSS; mixing zinc oxide with titanium dioxide sol, drying, and then reacting with trimethoxysilane and modified POSS in sequence to obtain a modified zinc oxide-titanium dioxide composite material; polymerizing an olefin mixed liquid to obtain a polyacrylate emulsion; mixing the polyacrylate emulsion and the modified zinc oxide-titanium dioxide composite material, spinning, and weaving to obtain a polyacrylate fabric; and reacting the polyacrylate fabric with aniline and a surface treatment liquid in sequence to obtain the antibacterial self-cleaning wall cloth.
[0025] First, methyltrimethoxysilane and allyltrimethoxysilane are reacted to obtain modified POSS; zinc oxide and titanium dioxide sol are mixed, dried, and then reacted with trimethoxysilane and modified POSS in sequence to obtain a modified zinc oxide titanium dioxide composite material; POSS material will form a dense silicon oxide film layer similar to a ceramic structure at high temperature, which effectively prevents the escape of small molecules and molten droplets produced after polymer decomposition, and isolates the transfer of oxygen and heat, thereby achieving a flame retardant effect; capture free radicals: and its silicon oxygen skeleton structure is stable, and can generate active groups that quench oxygen free radicals at high temperatures. These groups can capture and quench oxygen free radicals, thereby The chain reaction of combustion is interrupted to achieve the flame retardant effect; a layer of titanium dioxide film is loaded on the surface of zinc oxide. Titanium dioxide can generate photogenerated electrons and holes under light. These photogenerated electrons and holes react with water and oxygen adsorbed on the surface of titanium dioxide to generate hydroxyl free radicals and peroxyl free radicals with strong oxidizing properties. These free radicals can oxidize the organic matter adsorbed on the surface of titanium dioxide and decompose it into carbon dioxide and water, thereby achieving the effect of cleaning the surface; the zinc ions in nano zinc oxide will gradually become free, and when they come into contact with bacteria, they will combine with the active protease in the bacteria, making it inactive, thereby killing the bacteria and achieving the antibacterial effect.
[0026] Secondly, the olefin mixed liquid is polymerized to obtain a polyacrylate emulsion; the polyacrylate emulsion and the modified zinc oxide titanium dioxide composite material are mixed, spun, and woven to obtain a polyacrylate fabric; the polyacrylate fabric is reacted with aniline and a surface treatment liquid in sequence to obtain an antibacterial self-cleaning wall cloth; the amino groups at both ends of the polyaniline can react with the epoxy groups on the surface of the polyacrylate to load a layer of polyaniline on the surface of the fabric. Polyaniline is a conductive polymer. Conductive polymers usually contain conductive groups or conductive fillers. These components can form conductive channels inside the polymer, so that the entire material has a certain conductivity. When static electricity is generated, these conductive channels can effectively dissipate the charge and prevent static electricity accumulation; fluorine is connected to one side of the wall cloth using an initiator. Fluorine is a non-metallic element with strong electronegativity, an extremely small atomic radius, and a high electron cloud density, so it has a strong electrostatic attraction. These characteristics enable fluorine to form a stable chemical bond when combined with other elements, thereby showing extremely strong chemical inertness and physical inertness, thereby achieving a corrosion-resistant effect. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0028] Embodiment 1:
[0029] A method for preparing an antibacterial self-cleaning wall cloth mainly comprises the following preparation steps:
[0030] (1) Lithium hydroxide monohydrate, deionized water, acetone and methanol were mixed in a mass ratio of 4:3:170:23, stirred at 75°C and 200 r / min for 3 min, methyltrimethoxysilane with a mass of 11 times that of deionized water was added at a uniform rate within 5 min, sodium hydroxide solution with a mass of 62 times that of deionized water was added, stirring was continued for 100 min, filtered, washed with acetonitrile 4 times, and dried at 70°C for 10 h to obtain modified polysiloxane; modified polysiloxane was mixed with ethanol in a mass ratio of 1:4.5, stirred at 18°C and 200 r / min for 3 min, allyltrimethoxysilane with a mass of 0.04 times that of ethanol and tetraethylammonium hydroxide solution with a mass of 0.035 times that of ethanol were added at a uniform rate within 50 min, stirring was continued for 35 h, filtered, washed with acetonitrile 4 times to obtain modified POSS;
[0031] (2) Ethanol and deionized water were mixed in a mass ratio of 8:4 to obtain an ethanol aqueous solution; butyl titanate, diethanolamine and ethanol were mixed in a mass ratio of 1:1:17, stirred at 200 r / min for 8 minutes, and an ethanol aqueous solution with a mass of 13 times that of butyl titanate was added at a uniform rate within 8 minutes, and the stirring was continued for 30 minutes to obtain a titanium dioxide sol; zinc oxide was immersed in the titanium dioxide sol for 2 minutes, filtered, dried at 90°C for 8 minutes, and then kept at 490°C for 50 minutes to obtain a zinc oxide titanium dioxide composite material; The zinc oxide titanium dioxide composite material, trimethoxysilane and isopropanol were mixed in a mass ratio of 8:1:30, stirred at 85°C and 200 r / min for 5 hours, centrifuged to obtain a solid, washed with deionized water for 3 times, and dried at 90°C for 2 hours to obtain a pre-modified zinc oxide titanium dioxide composite material; the pre-modified zinc oxide titanium dioxide composite material, modified POSS, chloroplatinic acid and isopropanol were mixed in a mass ratio of 1:0.3:0.03:3, stirred at 60°C and 200 r / min for 4 hours to obtain a modified zinc oxide titanium dioxide composite material;
[0032] (3) Methyl methacrylate, isooctyl acrylate, glycidyl methacrylate and butyl acrylate were mixed uniformly in a mass ratio of 8:4:2:12 to obtain an olefin mixture; 4-methylcyclohexanone was heated to 140°C, and an olefin mixture of 3 times the mass of 4-methylcyclohexanone and azobisisobutyronitrile of 0.03 times the mass of the olefin mixture were uniformly added within 4 hours, and the temperature was raised to 145°C, and the reaction was continued for 100 minutes, and then the temperature was lowered to room temperature, and the pH was adjusted to 6.5 with dimethylethanolamine to obtain a polyacrylate emulsion;
[0033] (4) The polyacrylate emulsion and the modified zinc oxide titanium dioxide composite material are mixed uniformly in a mass ratio of 1:0.1 to obtain a spinning solution; the spinning solution is subjected to electrostatic spinning at a spinning flow rate of 0.18 ml / h, a spinning voltage of 16 KV, and a receiving distance of 14 cm, and allowed to stand for 6 hours, and naturally cooled to room temperature to obtain modified polyacrylate fibers, which are woven into fabrics to obtain polyacrylate fabrics;
[0034] (5) Aniline and water were mixed in a mass ratio of 1:9 to obtain an aniline aqueous solution; ammonium persulfate and deionized water were mixed in a mass ratio of 1:18 to obtain an ammonium persulfate aqueous solution; polyacrylate fabric was immersed in the aniline aqueous solution and ultrasonically treated for 50 minutes, and an ammonium persulfate aqueous solution of equal mass to the aniline aqueous solution was uniformly added within 160 minutes, the polyacrylate fabric was taken out, allowed to stand for 18 hours, washed with ethanol 3 times, and dried at -10°C for 22 hours to obtain a modified polyacrylate fabric; trifluoropropylene, xylene and diisopropylbenzene peroxide were mixed in a mass ratio of 1:18:0.6 to obtain a surface treatment liquid; 1 mL of the surface treatment liquid was uniformly applied on each square centimeter of the surface of the modified polyacrylate fabric, allowed to stand for 4 hours at 120°C under nitrogen protection, and the coating and drying were repeated 3 times, washed with acetone 3 times, and vacuum dried at -10°C for 22 hours to obtain a wall covering.
[0035] Embodiment 2:
[0036] A method for preparing an antibacterial self-cleaning wall cloth mainly comprises the following preparation steps:
[0037] (1) Lithium hydroxide monohydrate, deionized water, acetone and methanol were mixed in a mass ratio of 5:4:173:24, stirred at 80°C and 250 r / min for 4 min, methyltrimethoxysilane with a mass of 12 times that of deionized water was added at a uniform rate within 6 min, sodium hydroxide solution with a mass of 63.5 times that of deionized water was added, stirring was continued for 120 min, filtered, washed with acetonitrile 5 times, and dried at 75°C for 12 h to obtain modified polysiloxane; modified polysiloxane was mixed with ethanol in a mass ratio of 1:5, stirred at 20°C and 250 r / min for 4 min, allyltrimethoxysilane with a mass of 0.045 times that of ethanol and tetraethylammonium hydroxide solution with a mass of 0.04 times that of ethanol were added at a uniform rate within 60 min, stirring was continued for 36 h, filtered, washed with acetonitrile 5 times, and modified POSS was obtained;
[0038] (2) Ethanol and deionized water were mixed uniformly at a mass ratio of 8.5:5 to obtain an ethanol aqueous solution; butyl titanate, diethanolamine and ethanol were mixed at a mass ratio of 1:1.1:17.5, stirred at 250 r / min for 10 min, and an ethanol aqueous solution with a mass of 13.5 times that of butyl titanate was added uniformly within 9 min, and the stirring was continued for 35 min to obtain a titanium dioxide sol; zinc oxide was immersed in the titanium dioxide sol for 2.5 min, filtered, dried at 100°C for 10 min, and then kept at 510°C for 60 min to obtain a zinc oxide titanium dioxide composite. The composite material was prepared by mixing a zinc oxide titanium dioxide composite material, trimethoxysilane and isopropanol in a mass ratio of 10:1:40, stirring at 90°C and 250r / min for 6h, centrifuging and separating the solid, washing it with deionized water for 4 times, and drying it at 100°C for 3h to obtain a pre-modified zinc oxide titanium dioxide composite material; the pre-modified zinc oxide titanium dioxide composite material, modified POSS, chloroplatinic acid and isopropanol were mixed in a mass ratio of 1:0.4:0.04:3.2, stirring at 65°C and 250r / min for 5h to obtain a modified zinc oxide titanium dioxide composite material;
[0039] (3) Methyl methacrylate, isooctyl acrylate, glycidyl methacrylate and butyl acrylate were mixed uniformly in a mass ratio of 9:5:2.5:14 to obtain an olefin mixture; 4-methylcyclohexanone was heated to 142°C, and an olefin mixture of 4 times the mass of 4-methylcyclohexanone and azobisisobutyronitrile of 0.04 times the mass of the olefin mixture were uniformly added within 5 hours, and the temperature was raised to 150°C, and the reaction was continued for 120 minutes, and then the temperature was lowered to room temperature, and the pH was adjusted to 7 with dimethylethanolamine to obtain a polyacrylate emulsion;
[0040] (4) The polyacrylate emulsion and the modified zinc oxide titanium dioxide composite material are mixed uniformly in a mass ratio of 1:0.15 to obtain a spinning solution; the spinning solution is subjected to electrostatic spinning at a spinning flow rate of 0.2 ml / h, a spinning voltage of 17 KV, and a receiving distance of 15 cm, and allowed to stand for 7 hours, and naturally cooled to room temperature to obtain modified polyacrylate fibers, which are woven into fabrics to obtain polyacrylate fabrics;
[0041] (5) Aniline and water were mixed in a mass ratio of 1:10 to obtain an aniline aqueous solution; ammonium persulfate and deionized water were mixed in a mass ratio of 1:20 to obtain an ammonium persulfate aqueous solution; polyacrylate fabric was immersed in the aniline aqueous solution for 60 minutes under ultrasonic treatment, and an ammonium persulfate aqueous solution of the same mass as the aniline aqueous solution was added at a uniform rate within 180 minutes, the polyacrylate fabric was taken out, allowed to stand for 20 hours, washed with ethanol 4 times, and dried at -5°C for 23 hours to obtain a modified polyacrylate fabric; trifluoropropylene, xylene and diisopropylbenzene peroxide were mixed in a mass ratio of 1:20:0.7 to obtain a surface treatment liquid; 1.5 mL of the surface treatment liquid was evenly applied on each square centimeter of the surface of the modified polyacrylate fabric, allowed to stand for 4.5 hours at 130°C under nitrogen protection, and the coating and drying were repeated 4 times, washed with acetone 4 times, and vacuum dried at -5.5°C for 23 hours to obtain a wall covering.
[0042] Embodiment 3:
[0043] A method for preparing an antibacterial self-cleaning wall cloth mainly comprises the following preparation steps:
[0044] (1) Lithium hydroxide monohydrate, deionized water, acetone and methanol were mixed in a mass ratio of 6:5:176:25, stirred at 85°C and 300 r / min for 5 min, methyltrimethoxysilane with a mass of 13 times that of deionized water was added at a uniform rate within 7 min, sodium hydroxide solution with a mass of 65 times that of deionized water was added, stirring was continued for 140 min, filtered, washed with acetonitrile 6 times, and dried at 80°C for 14 h to obtain modified polysiloxane; modified polysiloxane was mixed with ethanol in a mass ratio of 1:5.5, stirred at 22°C and 300 r / min for 5 min, allyltrimethoxysilane with a mass of 0.05 times that of ethanol and tetraethylammonium hydroxide solution with a mass of 0.045 times that of ethanol were added at a uniform rate within 70 min, stirring was continued for 37 h, filtered, washed with acetonitrile 6 times, and modified POSS was obtained;
[0045] (2) Ethanol and deionized water were mixed uniformly in a mass ratio of 9:6 to obtain an ethanol aqueous solution; butyl titanate, diethanolamine and ethanol were mixed in a mass ratio of 1:1.2:18, stirred at 300 r / min for 12 min, and an ethanol aqueous solution 14 times the mass of butyl titanate was added at a uniform rate within 10 min, and the stirring was continued for 40 min to obtain a titanium dioxide sol; zinc oxide was immersed in the titanium dioxide sol for 3 min, filtered, dried at 110°C for 12 min, and then kept at 510°C for 70 min to obtain a zinc oxide titanium dioxide composite material; The zinc oxide titanium dioxide composite material, trimethoxysilane and isopropanol were mixed in a mass ratio of 12:1:50, stirred at 95°C and 300 r / min for 7 hours, centrifuged to obtain a solid, washed with deionized water for 5 times, and dried at 100°C for 4 hours to obtain a pre-modified zinc oxide titanium dioxide composite material; the pre-modified zinc oxide titanium dioxide composite material, modified POSS, chloroplatinic acid and isopropanol were mixed in a mass ratio of 1:0.5:0.05:3.4, stirred at 70°C and 300 r / min for 6 hours to obtain a modified zinc oxide titanium dioxide composite material;
[0046] (3) Methyl methacrylate, isooctyl acrylate, glycidyl methacrylate and butyl acrylate were mixed uniformly in a mass ratio of 10:6:3:16 to obtain an olefin mixture; 4-methylcyclohexanone was heated to 144°C, and an olefin mixture of 5 times the mass of 4-methylcyclohexanone and azobisisobutyronitrile of 0.05 times the mass of the olefin mixture were added at a uniform rate within 6 hours, and the temperature was raised to 155°C, and the reaction was continued for 140 minutes, and then the temperature was lowered to room temperature, and the pH was adjusted to 7.5 with dimethylethanolamine to obtain a polyacrylate emulsion;
[0047] (4) The polyacrylate emulsion and the modified zinc oxide titanium dioxide composite material are mixed uniformly in a mass ratio of 1:0.2 to obtain a spinning solution; the spinning solution is subjected to electrostatic spinning at a spinning flow rate of 0.22 ml / h, a spinning voltage of 18 KV, and a receiving distance of 16 cm, and allowed to stand for 8 hours, and naturally cooled to room temperature to obtain modified polyacrylate fibers, which are woven into fabrics to obtain polyacrylate fabrics;
[0048] (5) Aniline and water were mixed in a mass ratio of 1:11 to obtain an aniline aqueous solution; ammonium persulfate and deionized water were mixed in a mass ratio of 1:22 to obtain an ammonium persulfate aqueous solution; polyacrylate fabric was immersed in the aniline aqueous solution and ultrasonicated for 70 minutes, and an ammonium persulfate aqueous solution of equal mass to the aniline aqueous solution was added at a uniform rate within 200 minutes, the polyacrylate fabric was taken out, allowed to stand for 22 hours, washed with ethanol 5 times, and dried at 0°C for 24 hours to obtain a modified polyacrylate fabric; trifluoropropylene, xylene and diisopropylbenzene peroxide were mixed in a mass ratio of 1:22:0.8 to obtain a surface treatment liquid; 2 mL of the surface treatment liquid was evenly coated on each square centimeter of the modified polyacrylate fabric surface, allowed to stand for 5 hours at 140°C under nitrogen protection, and the coating and drying were repeated 5 times, washed with acetone 5 times, and vacuum dried at -1°C for 24 hours to obtain a wall cloth.
[0049] Comparative Example 1:
[0050] A method for preparing an antibacterial self-cleaning wall cloth mainly comprises the following preparation steps:
[0051] (1) Lithium hydroxide monohydrate, deionized water, acetone and methanol were mixed in a mass ratio of 5:4:173:24, stirred at 80°C and 250 r / min for 4 min, methyltrimethoxysilane with a mass of 12 times that of deionized water was added at a uniform rate within 6 min, sodium hydroxide solution with a mass of 63.5 times that of deionized water was added, stirring was continued for 120 min, filtered, washed with acetonitrile 5 times, and dried at 75°C for 12 h to obtain modified polysiloxane; modified polysiloxane was mixed with ethanol in a mass ratio of 1:5, stirred at 20°C and 250 r / min for 4 min, allyltrimethoxysilane with a mass of 0.045 times that of ethanol and tetraethylammonium hydroxide solution with a mass of 0.04 times that of ethanol were added at a uniform rate within 60 min, stirring was continued for 36 h, filtered, washed with acetonitrile 5 times, and modified POSS was obtained;
[0052] (2) Nano-titanium dioxide, trimethoxysilane and isopropanol were mixed in a mass ratio of 10:1:40, stirred at 90°C and 250 r / min for 6 h, centrifuged to obtain a solid, washed with deionized water 4 times, and dried at 100°C for 3 h to obtain pre-modified titanium dioxide; pre-modified titanium dioxide, modified POSS, chloroplatinic acid and isopropanol were mixed in a mass ratio of 1:0.4:0.04:3.2, stirred at 65°C and 250 r / min for 5 h to obtain modified titanium dioxide;
[0053] (3) Methyl methacrylate, isooctyl acrylate, glycidyl methacrylate and butyl acrylate were mixed uniformly in a mass ratio of 9:5:2.5:14 to obtain an olefin mixture; 4-methylcyclohexanone was heated to 142°C, and an olefin mixture of 4 times the mass of 4-methylcyclohexanone and azobisisobutyronitrile of 0.04 times the mass of the olefin mixture were uniformly added within 5 hours, and the temperature was raised to 150°C, and the reaction was continued for 120 minutes, and then the temperature was lowered to room temperature, and the pH was adjusted to 7 with dimethylethanolamine to obtain a polyacrylate emulsion;
[0054] (4) mixing polyacrylate emulsion and modified titanium dioxide in a mass ratio of 1:0.15 to obtain a spinning solution; electrospinning the spinning solution at a spinning flow rate of 0.2 ml / h, a spinning voltage of 17 KV, and a receiving distance of 15 cm, standing for 7 hours, and naturally cooling to room temperature to obtain modified polyacrylate fiber, which was woven into a fabric to obtain a polyacrylate fabric;
[0055] (5) Aniline and water were mixed in a mass ratio of 1:10 to obtain an aniline aqueous solution; ammonium persulfate and deionized water were mixed in a mass ratio of 1:20 to obtain an ammonium persulfate aqueous solution; polyacrylate fabric was immersed in the aniline aqueous solution for 60 minutes under ultrasonic treatment, and an ammonium persulfate aqueous solution of the same mass as the aniline aqueous solution was added at a uniform rate within 180 minutes, the polyacrylate fabric was taken out, allowed to stand for 20 hours, washed with ethanol 4 times, and dried at -5°C for 23 hours to obtain a modified polyacrylate fabric; trifluoropropylene, xylene and diisopropylbenzene peroxide were mixed in a mass ratio of 1:20:0.7 to obtain a surface treatment liquid; 1.5 mL of the surface treatment liquid was evenly applied on each square centimeter of the surface of the modified polyacrylate fabric, allowed to stand for 4.5 hours at 130°C under nitrogen protection, and the coating and drying were repeated 4 times, washed with acetone 4 times, and vacuum dried at -5.5°C for 23 hours to obtain a wall covering.
[0056] Comparative Example 2:
[0057] A method for preparing an antibacterial self-cleaning wall cloth mainly comprises the following preparation steps:
[0058] (1) Lithium hydroxide monohydrate, deionized water, acetone and methanol were mixed in a mass ratio of 5:4:173:24, stirred at 80°C and 250 r / min for 4 min, methyltrimethoxysilane with a mass of 12 times that of deionized water was added at a uniform rate within 6 min, sodium hydroxide solution with a mass of 63.5 times that of deionized water was added, stirring was continued for 120 min, filtered, washed with acetonitrile 5 times, and dried at 75°C for 12 h to obtain modified polysiloxane; modified polysiloxane was mixed with ethanol in a mass ratio of 1:5, stirred at 20°C and 250 r / min for 4 min, allyltrimethoxysilane with a mass of 0.045 times that of ethanol and tetraethylammonium hydroxide solution with a mass of 0.04 times that of ethanol were added at a uniform rate within 60 min, stirring was continued for 36 h, filtered, washed with acetonitrile 5 times, and modified POSS was obtained;
[0059] (2) zinc oxide, trimethoxysilane and isopropanol were mixed in a mass ratio of 10:1:40, stirred at 90°C and 250 r / min for 6 h, centrifuged to obtain a solid, washed with deionized water 4 times, and dried at 100°C for 3 h to obtain pre-modified zinc oxide; pre-modified zinc oxide, modified POSS, chloroplatinic acid and isopropanol were mixed in a mass ratio of 1:0.4:0.04:3.2, stirred at 65°C and 250 r / min for 5 h to obtain modified zinc oxide;
[0060] (3) Methyl methacrylate, isooctyl acrylate, glycidyl methacrylate and butyl acrylate were mixed uniformly in a mass ratio of 9:5:2.5:14 to obtain an olefin mixture; 4-methylcyclohexanone was heated to 142°C, and an olefin mixture of 4 times the mass of 4-methylcyclohexanone and azobisisobutyronitrile of 0.04 times the mass of the olefin mixture were uniformly added within 5 hours, and the temperature was raised to 150°C, and the reaction was continued for 120 minutes, and then the temperature was lowered to room temperature, and the pH was adjusted to 7 with dimethylethanolamine to obtain a polyacrylate emulsion;
[0061] (4) mixing polyacrylate emulsion and modified zinc oxide in a mass ratio of 1:0.15 to obtain a spinning solution; electrospinning the spinning solution at a spinning flow rate of 0.2 ml / h, a spinning voltage of 17 KV, and a receiving distance of 15 cm, standing for 7 hours, and naturally cooling to room temperature to obtain modified polyacrylate fiber, which was woven into a fabric to obtain a polyacrylate fabric;
[0062] (5) Aniline and water were mixed in a mass ratio of 1:10 to obtain an aniline aqueous solution; ammonium persulfate and deionized water were mixed in a mass ratio of 1:20 to obtain an ammonium persulfate aqueous solution; polyacrylate fabric was immersed in the aniline aqueous solution for 60 minutes under ultrasonic treatment, and an ammonium persulfate aqueous solution of the same mass as the aniline aqueous solution was added at a uniform rate within 180 minutes, the polyacrylate fabric was taken out, allowed to stand for 20 hours, washed with ethanol 4 times, and dried at -5°C for 23 hours to obtain a modified polyacrylate fabric; trifluoropropylene, xylene and diisopropylbenzene peroxide were mixed in a mass ratio of 1:20:0.7 to obtain a surface treatment liquid; 1.5 mL of the surface treatment liquid was evenly applied on each square centimeter of the surface of the modified polyacrylate fabric, allowed to stand for 4.5 hours at 130°C under nitrogen protection, and the coating and drying were repeated 4 times, washed with acetone 4 times, and vacuum dried at -5.5°C for 23 hours to obtain a wall covering.
[0063] Comparative Example 3:
[0064] A method for preparing an antibacterial self-cleaning wall cloth mainly comprises the following preparation steps:
[0065] (1) Butyl titanate, diethanolamine and ethanol were mixed in a mass ratio of 1:1.1:17.5, stirred at 250 r / min for 10 min, and an ethanol aqueous solution 13.5 times the mass of butyl titanate was uniformly added within 9 min, and the stirring was continued for 35 min to obtain a titanium dioxide sol; zinc oxide was immersed in the titanium dioxide sol for 2.5 min, filtered, dried at 100°C for 10 min, and then kept at 510°C for 60 min to obtain a zinc oxide titanium dioxide composite material;
[0066] (2) Methyl methacrylate, isooctyl acrylate, glycidyl methacrylate and butyl acrylate were mixed uniformly in a mass ratio of 9:5:2.5:14 to obtain an olefin mixture; 4-methylcyclohexanone was heated to 142°C, and an olefin mixture of 4 times the mass of 4-methylcyclohexanone and azobisisobutyronitrile of 0.04 times the mass of the olefin mixture were uniformly added within 5 hours, and the temperature was raised to 150°C, and the reaction was continued for 120 minutes, and then the temperature was lowered to room temperature, and the pH was adjusted to 7 with dimethylethanolamine to obtain a polyacrylate emulsion;
[0067] (3) The polyacrylate emulsion and the zinc oxide titanium dioxide composite material are mixed uniformly in a mass ratio of 1:0.15 to obtain a spinning solution; the spinning solution is subjected to electrostatic spinning at a spinning flow rate of 0.2 ml / h, a spinning voltage of 17 KV, and a receiving distance of 15 cm, and allowed to stand for 7 hours, and naturally cooled to room temperature to obtain modified polyacrylate fibers, which are woven into fabrics to obtain polyacrylate fabrics;
[0068] (4) Aniline and water were mixed in a mass ratio of 1:10 to obtain an aniline aqueous solution; ammonium persulfate and deionized water were mixed in a mass ratio of 1:20 to obtain an ammonium persulfate aqueous solution; polyacrylate fabric was immersed in the aniline aqueous solution for 60 minutes under ultrasonic treatment, and an ammonium persulfate aqueous solution of the same mass as the aniline aqueous solution was added at a uniform rate within 180 minutes, the polyacrylate fabric was taken out, allowed to stand for 20 hours, washed with ethanol 4 times, and dried at -5°C for 23 hours to obtain a modified polyacrylate fabric; trifluoropropylene, xylene and diisopropylbenzene peroxide were mixed in a mass ratio of 1:20:0.7 to obtain a surface treatment liquid; 1.5 mL of the surface treatment liquid was evenly coated on each square centimeter of the modified polyacrylate fabric surface, allowed to stand for 4.5 hours at 130°C under nitrogen protection, and the coating and drying were repeated 4 times, washed with acetone 4 times, and vacuum dried at -5.5°C for 23 hours to obtain a wall covering.
[0069] Comparative Example 4
[0070] A method for preparing an antibacterial self-cleaning wall cloth mainly comprises the following preparation steps:
[0071] (1) Lithium hydroxide monohydrate, deionized water, acetone and methanol were mixed in a mass ratio of 5:4:173:24, stirred at 80°C and 250 r / min for 4 min, methyltrimethoxysilane with a mass of 12 times that of deionized water was added at a uniform rate within 6 min, sodium hydroxide solution with a mass of 63.5 times that of deionized water was added, stirring was continued for 120 min, filtered, washed with acetonitrile 5 times, and dried at 75°C for 12 h to obtain modified polysiloxane; modified polysiloxane was mixed with ethanol in a mass ratio of 1:5, stirred at 20°C and 250 r / min for 4 min, allyltrimethoxysilane with a mass of 0.045 times that of ethanol and tetraethylammonium hydroxide solution with a mass of 0.04 times that of ethanol were added at a uniform rate within 60 min, stirring was continued for 36 h, filtered, washed with acetonitrile 5 times, and modified POSS was obtained;
[0072] (2) Ethanol and deionized water were mixed uniformly at a mass ratio of 8.5:5 to obtain an ethanol aqueous solution; butyl titanate, diethanolamine and ethanol were mixed at a mass ratio of 1:1.1:17.5, stirred at 250 r / min for 10 min, and an ethanol aqueous solution with a mass of 13.5 times that of butyl titanate was added uniformly within 9 min, and the stirring was continued for 35 min to obtain a titanium dioxide sol; zinc oxide was immersed in the titanium dioxide sol for 2.5 min, filtered, dried at 100°C for 10 min, and then kept at 510°C for 60 min to obtain a zinc oxide titanium dioxide composite. The composite material was prepared by mixing a zinc oxide titanium dioxide composite material, trimethoxysilane and isopropanol in a mass ratio of 10:1:40, stirring at 90°C and 250r / min for 6h, centrifuging and separating the solid, washing it with deionized water for 4 times, and drying it at 100°C for 3h to obtain a pre-modified zinc oxide titanium dioxide composite material; the pre-modified zinc oxide titanium dioxide composite material, modified POSS, chloroplatinic acid and isopropanol were mixed in a mass ratio of 1:0.4:0.04:3.2, stirring at 65°C and 250r / min for 5h to obtain a modified zinc oxide titanium dioxide composite material;
[0073] (3) Methyl methacrylate, isooctyl acrylate, glycidyl methacrylate and butyl acrylate were mixed uniformly in a mass ratio of 9:5:2.5:14 to obtain an olefin mixture; 4-methylcyclohexanone was heated to 142°C, and an olefin mixture of 4 times the mass of 4-methylcyclohexanone and azobisisobutyronitrile of 0.04 times the mass of the olefin mixture were uniformly added within 5 hours, and the temperature was raised to 150°C, and the reaction was continued for 120 minutes, and then the temperature was lowered to room temperature, and the pH was adjusted to 7 with dimethylethanolamine to obtain a polyacrylate emulsion;
[0074] (4) The polyacrylate emulsion and the modified zinc oxide titanium dioxide composite material are mixed uniformly in a mass ratio of 1:0.15 to obtain a spinning solution; the spinning solution is subjected to electrostatic spinning at a spinning flow rate of 0.2 ml / h, a spinning voltage of 17 KV, and a receiving distance of 15 cm, and allowed to stand for 7 hours, and naturally cooled to room temperature to obtain modified polyacrylate fibers, which are woven into fabrics to obtain polyacrylate fabrics;
[0075] (5) Trifluoropropylene, xylene and diisopropylbenzene peroxide were mixed uniformly in a mass ratio of 1:20:0.7 to prepare a surface treatment liquid; 1.5 mL of the surface treatment liquid was evenly coated on each square centimeter of the polyacrylate fabric surface, and the mixture was allowed to stand for 4.5 hours at 130°C under nitrogen protection, and the coating and drying were repeated 4 times, and the mixture was washed with acetone 4 times, and vacuum dried at -5.5°C for 23 hours to prepare a wall covering.
[0076] Comparative Example 5
[0077] A method for preparing an antibacterial self-cleaning wall cloth mainly comprises the following preparation steps:
[0078] (1) Ethanol and deionized water were mixed in a mass ratio of 8.5:5 to obtain an ethanol aqueous solution; lithium hydroxide monohydrate, deionized water, acetone and methanol were mixed in a mass ratio of 5:4:173:24, stirred at 80°C and 250 r / min for 4 min, methyltrimethoxysilane with a mass of 12 times that of deionized water was added at a uniform rate within 6 min, sodium hydroxide solution with a mass of 63.5 times that of deionized water was added, stirring was continued for 120 min, filtered, washed with acetonitrile 5 times, and dried at 75°C for 12 h to obtain modified polysiloxane; modified polysiloxane was mixed with ethanol in a mass ratio of 1:5, stirred at 20°C and 250 r / min for 4 min, allyltrimethoxysilane with a mass of 0.045 times that of ethanol and tetraethylammonium hydroxide solution with a mass of 0.04 times that of ethanol were added at a uniform rate within 60 min, stirring was continued for 36 h, filtered, washed with acetonitrile 5 times, and modified POSS was obtained;
[0079] (2) Butyl titanate, diethanolamine and ethanol were mixed in a mass ratio of 1:1.1:17.5, stirred at 250 r / min for 10 min, and an ethanol aqueous solution with a mass of 13.5 times that of the butyl titanate was added at a uniform rate within 9 min, and the stirring was continued for 35 min to obtain a titanium dioxide sol; zinc oxide was immersed in the titanium dioxide sol for 2.5 min, filtered, dried at 100°C for 10 min, and then kept at 510°C for 60 min to obtain a zinc oxide titanium dioxide composite material; the zinc oxide titanium dioxide composite material The pre-modified zinc oxide titanium dioxide composite material was prepared by mixing the pre-modified zinc oxide titanium dioxide composite material, the modified POSS, chloroplatinic acid and isopropanol in a mass ratio of 1:0.4:0.04:3.2, stirring at 65°C and 250r / min for 5h, centrifuging and separating the solid, washing it with deionized water for 4 times, and drying it at 100°C for 3h to obtain the pre-modified zinc oxide titanium dioxide composite material; the pre-modified zinc oxide titanium dioxide composite material, the modified POSS, chloroplatinic acid and isopropanol in a mass ratio of 1:0.4:0.04:3.2 were mixed, stirred at 65°C and 250r / min for 5h to obtain the modified zinc oxide titanium dioxide composite material;
[0080] (3) Methyl methacrylate, isooctyl acrylate, glycidyl methacrylate and butyl acrylate were mixed uniformly in a mass ratio of 9:5:2.5:14 to obtain an olefin mixture; 4-methylcyclohexanone was heated to 142°C, and an olefin mixture of 4 times the mass of 4-methylcyclohexanone and azobisisobutyronitrile of 0.04 times the mass of the olefin mixture were uniformly added within 5 hours, and the temperature was raised to 150°C, and the reaction was continued for 120 minutes, and then the temperature was lowered to room temperature, and the pH was adjusted to 7 with dimethylethanolamine to obtain a polyacrylate emulsion;
[0081] (4) The polyacrylate emulsion and the modified zinc oxide titanium dioxide composite material are mixed uniformly in a mass ratio of 1:0.15 to obtain a spinning solution; the spinning solution is subjected to electrostatic spinning at a spinning flow rate of 0.2 ml / h, a spinning voltage of 17 KV, and a receiving distance of 15 cm, and allowed to stand for 7 hours, and naturally cooled to room temperature to obtain modified polyacrylate fibers, which are woven into fabrics to obtain polyacrylate fabrics;
[0082] (5) Aniline and water were mixed in a mass ratio of 1:10 to obtain an aniline aqueous solution; ammonium persulfate and deionized water were mixed in a mass ratio of 1:20 to obtain an ammonium persulfate aqueous solution; polyacrylate fabric was immersed in the aniline aqueous solution and ultrasonicated for 60 minutes, and an ammonium persulfate aqueous solution with an equal mass of the aniline aqueous solution was added at a uniform rate within 180 minutes, the polyacrylate fabric was taken out, allowed to stand for 20 hours, washed with ethanol 4 times, and dried at -5°C for 23 hours to obtain a wall covering.
[0083] Test Example 1:
[0084] Flame retardancy test: The limiting oxygen index was tested according to GB / T5454 test standard. The results are shown in Table 1.
[0085] Table 1
[0086] Limiting oxygen index Example 1 29.8% Example 2 29.7% Example 3 29.5% Comparative Example 1 29.9% Comparative Example 2 29.6% Comparative Example 3 23.8% Comparative Example 4 29.4% Comparative Example 5 29.7%
[0087] From the comparison of the experimental data in Table 1, it can be found that the antibacterial self-cleaning wall cloth prepared by the present invention has good flame retardancy.
[0088] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3 in Table 1, it can be found that the limiting oxygen index of Examples 1, 2, 3 is larger than that of Comparative Example 3, which shows that the POSS material will form a dense silicon oxide film layer similar to a ceramic structure at high temperature, effectively preventing the escape of small molecules and molten droplets produced after polymer cracking, while isolating the transfer of oxygen and heat, thereby achieving a flame retardant effect; capturing free radicals: and its silicon-oxygen skeleton structure is stable, and active groups that quench oxygen free radicals can be generated at high temperatures. These groups can capture and quench oxygen free radicals, thereby interrupting the chain reaction of combustion, achieving a flame retardant effect, and increasing the limiting oxygen index of the material.
[0089] Test Example 2:
[0090] Antimicrobial Testing:
[0091] The fiber was tested according to the GB / T20944 oscillation method, where the selected bacteria were Staphylococcus aureus and Escherichia coli. The results are shown in Table 2.
[0092] Table 2
[0093] Staphylococcus aureus Escherichia coli Example 1 99.9% 99.9% Example 2 99.9% 99.9% Example 3 99.9% 99.9% Comparative Example 1 99.0% 98.8% Comparative Example 2 99.9% 99.9% Comparative Example 3 99.9% 99.9% Comparative Example 4 99.9% 99.9% Comparative Example 5 99.9% 99.9%
[0094] From the comparison of the experimental data in Table 2, it can be found that the antibacterial self-cleaning wall cloth prepared by the present invention has good antibacterial ability.
[0095] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1 in Table 2, it can be found that the antibacterial rates of Examples 1, 2, 3 are higher than those of Comparative Example 1, which indicates that the zinc ions in the nano zinc oxide will gradually be freed. When they come into contact with bacteria, they will combine with the active protease in the bacteria to make them lose their activity, thereby killing the bacteria and achieving an antibacterial effect.
[0096] Test Example 3:
[0097] Self-cleaning test:
[0098] UV light source: main peak wavelength 297nm, radiation intensity 60W / m; pollutant preparation: take 0.01g methylene blue, add 10ml deionized water and 20ml 14# engine oil, stir at 200r / min for 10min; cut each example and comparative example into a rectangle of 2*5*0.3cm, immerse in the pollutant for 20 seconds and immediately observe whether the methylene blue fades. The results are shown in Table 3.
[0099] Table 3
[0100] Is it faded? Example 1 yes Example 2 yes Example 3 yes Comparative Example 1 yes Comparative Example 2 no Comparative Example 3 yes Comparative Example 4 yes Comparative Example 5 yes
[0101] From the comparison of the experimental data in Table 3, it can be found that the antibacterial self-cleaning wall cloth prepared by the present invention has good self-cleaning ability.
[0102] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 2 in Table 3, it can be found that Examples 1, 2, 3 faded compared with Comparative Example 2, which shows that titanium dioxide can generate photogenerated electrons and holes under light. These photogenerated electrons and holes react with water and oxygen adsorbed on the surface of titanium dioxide to generate hydroxyl radicals and peroxyl radicals with strong oxidizing properties. These free radicals can oxidize organic matter adsorbed on the surface of titanium dioxide and decompose it into carbon dioxide and water, thereby achieving the effect of cleaning the surface.
[0103] Test Example 4:
[0104] Corrosion resistance test:
[0105] At 37°C, 0.1 g of artificial sweat was applied per square centimeter on the side of the fabric coated with the surface treatment liquid, and the surface was left to stand for 3 days to test the mass retention rate, where the mass retention rate = mass before coating / mass after coating * 100%. The results are shown in Table 4.
[0106] Table 4
[0107] Quality retention rate Example 1 99.3% Example 2 99.4% Example 3 99.2% Comparative Example 1 99.0% Comparative Example 2 99.1% Comparative Example 3 99.4% Comparative Example 4 99.2% Comparative Example 5 98.5%
[0108] From the comparison of the experimental data in Table 4, it can be found that the antibacterial self-cleaning wall cloth prepared by the present invention has good corrosion resistance.
[0109] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 5 in Table 4, it can be found that the mass retention rates of Examples 1, 2, 3 are greater than those of Comparative Example 5, which shows that fluorine is a non-metallic element with strong electronegativity, extremely small atomic radius, and high electron cloud density, and therefore has a strong electrostatic attraction. These characteristics enable fluorine to form stable chemical bonds when combined with other elements, thereby showing extremely strong chemical inertness and physical inertness, thereby achieving a corrosion-resistant effect.
[0110] Test Example 5:
[0111] Antistatic test:
[0112] The surface resistivity of the samples was measured using a surface resistance tester. The results are shown in Table 5.
[0113] Table 5
[0114] Surface resistivity Example 1 6.793E+8Ω Example 2 6.811E+8Ω Example 3 6.805E+8Ω Comparative Example 1 6.799E+8Ω Comparative Example 2 6.832E+8Ω Comparative Example 3 6.841E+8Ω Comparative Example 4 1.005E+10Ω Comparative Example 5 6.837E+8Ω
[0115] From the comparison of the experimental data in Table 5, it can be found that the antibacterial self-cleaning wall cloth prepared by the present invention has good antistatic ability.
[0116] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4 in Table 5, it can be found that the surface resistivity of Examples 1, 2, 3 is smaller than that of Comparative Example 4, which shows that polyaniline is a conductive polymer. Conductive polymers usually contain conductive groups or conductive fillers. These components can form conductive channels inside the polymer, so that the entire material has a certain conductivity. When static electricity is generated, these conductive channels can effectively dissipate the charge and prevent static electricity accumulation.
[0117] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. An antibacterial self-cleaning wall cloth, characterized in that: The antibacterial self-cleaning wall cloth is prepared by reacting polyacrylate fabric with aniline and surface treatment liquid in sequence; The polyacrylate fabric is prepared by mixing polyacrylate emulsion and modified zinc oxide titanium dioxide composite material, spinning and weaving; The polyacrylate emulsion is prepared by polymerizing an olefin mixed liquid; The modified zinc oxide titanium dioxide composite material is prepared by mixing zinc oxide and titanium dioxide sol, drying, and then reacting with trimethoxysilane and modified POSS in sequence; The modified POSS is prepared by reacting methyltrimethoxysilane and allyltrimethoxysilane.
2. A method for preparing an antibacterial self-cleaning wall cloth, characterized in that: The preparation method of the antibacterial self-cleaning wall cloth mainly comprises the following preparation steps: (1) Lithium hydroxide monohydrate, deionized water, acetone and methanol are mixed in a mass ratio of 4-6:3-5:170-176:23-25, stirred at 75-85°C and 200-300 r / min for 3-5 minutes, methyltrimethoxysilane with a mass of 11-13 times the mass of deionized water is added at a uniform rate within 5-7 minutes, sodium hydroxide solution with a mass of 62-65 times the mass of deionized water is added, stirring is continued for 100-140 minutes, filtered, washed with acetonitrile for 4-6 times, and heated at 70-80°C. Drying for 10 to 14 hours to obtain modified polysiloxane; mixing the modified polysiloxane with ethanol in a mass ratio of 1:4.5 to 5.5, stirring at 18 to 22°C and 200 to 300 r / min for 3 to 5 minutes, uniformly adding allyl trimethoxy silane in an amount of 0.04 to 0.05 times the mass of ethanol and tetraethyl ammonium hydroxide solution in an amount of 0.035 to 0.045 times the mass of ethanol within 50 to 70 minutes, continuing stirring for 35 to 37 hours, filtering, and washing with acetonitrile for 4 to 6 times to obtain modified POSS; (2) mixing butyl titanate, diethanolamine and ethanol in a mass ratio of 1:1-1.2:17-18, stirring at 200-300 r / min for 8-12 min, adding ethanol aqueous solution 13-14 times the mass of butyl titanate at a uniform rate within 8-10 min, and continuing stirring for 30-40 min to obtain titanium dioxide sol; immersing zinc oxide in the titanium dioxide sol for 2-3 min, filtering, drying at 90-110° C. for 8-12 min, and then The mixture is kept at 490-510°C for 50-70 minutes to obtain a zinc oxide-titanium dioxide composite material; the zinc oxide-titanium dioxide composite material, trimethoxysilane and isopropanol are mixed in a mass ratio of 8-12:1:30-50, stirred at 85-95°C and 200-300 r / min for 5-7 hours, centrifuged to obtain a solid, washed with deionized water for 3-5 times, and dried at 90-100°C for 2-4 hours to obtain a pre-modified zinc oxide-titanium dioxide composite material; The pre-modified zinc oxide titanium dioxide composite material, modified POSS, chloroplatinic acid and isopropanol are mixed in a mass ratio of 1: 0.3-0.5: 0.03-0.05: 3-3.4, and stirred at 60-70° C. and 200-300 r / min for 4-6 hours to obtain a modified zinc oxide titanium dioxide composite material; (3) heating 4-methylcyclohexanone to 140-144° C., adding 3-5 times the mass of 4-methylcyclohexanone olefin mixture and 0.03-0.05 times the mass of olefin mixture at a uniform rate over 4-6 hours, heating to 145-155° C., continuing the reaction for 100-140 minutes, then cooling to room temperature, and adjusting the pH to 6.5-7.5 with dimethylethanolamine to obtain a polyacrylate emulsion; (4) electrospinning the spinning solution at a spinning flow rate of 0.18 to 0.22 ml / h, a spinning voltage of 16 to 18 kV, and a receiving distance of 14 to 16 cm, standing for 6 to 8 hours, and naturally cooling to room temperature to obtain modified polyacrylate fiber, which is woven into a fabric to obtain a polyacrylate fabric; (5) The polyacrylate fabric is immersed in an aniline aqueous solution and ultrasonically treated for 50 to 70 minutes. An ammonium persulfate aqueous solution of equal mass to the aniline aqueous solution is added at a uniform rate within 160 to 200 minutes. The polyacrylate fabric is taken out and allowed to stand for 18 to 22 hours. The polyacrylate fabric is washed with ethanol for 3 to 5 times and dried at -10 to 0°C for 22 to 24 hours to obtain a modified polyacrylate fabric. 1 to 2 mL of the surface treatment liquid is evenly coated on each square centimeter of the surface of the modified polyacrylate fabric. The surface is allowed to stand for 4 to 5 hours at 120 to 140°C under nitrogen protection. The coating and drying are repeated for 3 to 5 times. The fabric is washed with acetone for 3 to 5 times and vacuum dried at -10 to -1°C for 22 to 24 hours to obtain a wall covering.
3. The method for preparing an antibacterial self-cleaning wall cloth according to claim 2, characterized in that: The ethanol aqueous solution in step (2) is prepared by uniformly mixing ethanol and deionized water in a mass ratio of 8-9:4-6.
4. The method for preparing an antibacterial self-cleaning wall cloth according to claim 2, characterized in that: The zinc oxide in step (2) is nano zinc oxide with a particle size of 50 nm.
5. The method for preparing an antibacterial self-cleaning wall cloth according to claim 2, characterized in that: The olefin mixed liquid in step (3) is prepared by uniformly mixing methyl methacrylate, isooctyl acrylate, glycidyl methacrylate and butyl acrylate in a mass ratio of 8-10:4-6:2-3:12-16.
6. The method for preparing an antibacterial self-cleaning wall cloth according to claim 2, characterized in that: The spinning solution in step (4) is prepared by uniformly mixing polyacrylate emulsion and modified zinc oxide titanium dioxide composite material in a mass ratio of 1:0.1-0.
2.
7. The method for preparing an antibacterial self-cleaning wall cloth according to claim 2, characterized in that: The aniline aqueous solution in step (5) is prepared by uniformly mixing aniline and water in a mass ratio of 1:9 to 11.
8. The method for preparing an antibacterial self-cleaning wall cloth according to claim 2, characterized in that: The ammonium persulfate aqueous solution in step (5) is prepared by uniformly mixing ammonium persulfate and deionized water in a mass ratio of 1:18-22.
9. The method for preparing an antibacterial self-cleaning wall cloth according to claim 2, characterized in that: The surface treatment liquid in step (5) is prepared by uniformly mixing trifluoropropylene, xylene and diisopropylbenzene peroxide in a mass ratio of 1:18-22:0.6-0.8.